Serum NFL and tau, but not serum UCHL-1 and GFAP or CSF SNAP-25, NPTX2, or sTREM2, correlate with delirium in a 3-year retrospective analysis - Piel, Johannes Heinrich Alexander; Bargemann, Leon; Leypoldt, Frank; Wandinger, Klaus-Peter; Dargvainiene, Justina (Frontiers in Neurology, 2024)
Delirium represents a common terminal pathway of heterogeneous neurological conditions characterized by disturbances in consciousness and attention. Contemporary theories highlight the acute impairment of synaptic function and network connectivity, driven by neuroinflammation, oxidative stress and neurotransmitter imbalances. However, established biomarkers are still missing. Innovative diagnostic techniques, such as single-molecule array analysis, enable the detection of biomarkers in blood at picomolar concentrations. This approach paves the way for deeper insights into delirium and potentially therapeutic targets for tailored medical treatments. In a retrospective 3year study, we investigated seven biomarkers indicative of neuroaxonal damage (neurofilament light chain (NFL), Ubiquitin carboxyl-terminal hydrolase (UCHL-1) and tau protein), microglial activation (glial fibrillary acidic protein (GFAP), soluble triggering receptor expressed on myeloid cells 2 (sTREM2)) and synaptic dysfunction (synaptosomal-associated protein 25 (SNAP-25), neuronal pentraxin 2 (NPTX2)). The analysis of 71 patients with delirium, Alzheimer's disease (AD), and non-AD controls revealed that serum NFL levels are higher in delirium cases compared to both AD and non-AD. This suggests elevated NFL levels in delirium are not exclusively the result of dementiarelated damage. Serum tau levels were also elevated in delirium cases compared to controls. Conversely, cerebrospinal fluid (CSF) SNAP-25 showed higher levels in AD patients compared to controls only. These findings add to the increasing body of evidence suggesting that serum NFL could be a valuable biomarker of neuroaxonal damage in delirium research. Although SNAP-25 and NPTX2 did not exhibit significant differences in delirium, the exploration of synaptic biomarkers remains promising for enhancing our understanding of this condition.